2013
DOI: 10.1074/jbc.m112.416933
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Flexibility of Cyanobacterial Thylakoid Membranes Examined by Neutron Scattering

Abstract: Background:In cyanobacteria, light harvesting and photosynthesis occur in the thylakoid membranes. Results:The distances between thylakoid membranes are correlated with the size of the phycobilisome antenna and change reversibly and rapidly upon illumination. Conclusion: Thylakoid membranes have a structural plasticity tied to the regulation of photosynthesis. Significance: Characterizing the structural changes in photosynthetic membranes is crucial for understanding light harvesting and photosynthetic product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 22 publications
9
100
1
Order By: Relevance
“…In general, these results, in line with similar observations [29,39,[41][42][43], underline the remarkable flexibility of the thylakoid membrane ultrastructure, which should thus not be portrayed as simply providing a scaffold for the photosynthetic functions but also actively participating in the energy conversion steps and in different regulatory functions.…”
Section: Resultssupporting
confidence: 78%
“…In general, these results, in line with similar observations [29,39,[41][42][43], underline the remarkable flexibility of the thylakoid membrane ultrastructure, which should thus not be portrayed as simply providing a scaffold for the photosynthetic functions but also actively participating in the energy conversion steps and in different regulatory functions.…”
Section: Resultssupporting
confidence: 78%
“…In cyanobacteria, PSI turnover in PSI-enriched membrane domains requires that reduced plastocyanin or cytochrome c 6 molecules, generated by distal cytb 6 f complexes in the mixed membrane zones, diffuse to their docking sites on the lumenal side of the PSI array. Given that cyanobacterial thylakoids are closely appressed, and enclose a lumen of 5 to 9 nm (van de Meene et al, 2006;Liberton et al, 2013b), plastocyanin migration from cytb 6 f complexes and reduction of the PSI in large arrays might be impeded, as in plants. The cytochrome c 6 to PSI ratio for T. elongatus, for example, has been determined as 1.7 (Nguyen et al, 2017), so ensuring that they are oxidized by one of the PSI complexes in an array could be important.…”
Section: Discussionmentioning
confidence: 99%
“…Well-defined Bragg diffraction peaks were previously reported between 0.02 and 0.035 Å -1 in isolated granal chloroplasts, cyanobacteria, and diatoms (11,18). However, SANS experiments on the dark-adapted WT Chlamydomonas cells could not reveal any distinct Bragg diffraction peak, but only a shoulder at ∼0.035 Å -1 , indicating a poorly defined RD of ∼180 Å (Fig.…”
Section: Small-angle Neutron Scattering Measurements Indicate That Statementioning
confidence: 67%
“…Earlier experiments performed on cyanobacterial and diatom cells (11,12,18) have shown that light exposure induces darkreversible changes in the thylakoid-membrane ultrastructure, affecting both the Bragg peaks and the high-Q peak, without inducing ST. To verify the existence of this phenomenon in Chlamydomonas, we performed experiments on the stt7-9 mutant, which is unable to perform STs (20). In dark-adapted stt7-9 cells, a strong Bragg peak at 0.033 Å -1 (RD = 190 Å) was found (Fig.…”
Section: Small-angle Neutron Scattering Measurements Indicate That Statementioning
confidence: 99%